2020
DOI: 10.1177/1420326x19894037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on heat transfer of soil with different moisture contents and seepage for ground source heat pump

Abstract: Geothermal energy is a renewable energy source for heating, ventilating and air-conditioning (HVAC) systems, and is leveraged by ground heat exchanger (GHE) which is a key element of ground source heat pump (GSHP). The performance of GHE is significantly affected by soil thermal properties. To explore the heat transfer characteristics of soils with different moisture contents (MC) and seepage, a well-controlled sandbox was established and a series of experiments were performed. The results demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Two additional important sustainable applications related to groundwater flow are geothermal systems and underground thermal energy storage (UTES) systems [48][49][50][51][52][53][54][55][56][57][58][59]. These systems were first used due to the oil crisis of the 1970s to identify alternative sources of energy [60,61], and have subsequently been proven to be successful in solving various challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional important sustainable applications related to groundwater flow are geothermal systems and underground thermal energy storage (UTES) systems [48][49][50][51][52][53][54][55][56][57][58][59]. These systems were first used due to the oil crisis of the 1970s to identify alternative sources of energy [60,61], and have subsequently been proven to be successful in solving various challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [72] performed sandbox experiments encompassing dry, unsaturated, saturated, and seepage sand conditions. Figure 16 presents the heating temperature and capacity of the electric heating rod under dry, unsaturated, saturated, and seepage sand Different from the approach adopted by Li et al [71], which involved using a U-shaped tube as the heat exchanger and constant-temperature water tanks on both sides of the sandbox to facilitate horizontal seepage flow, Wang et al [72] developed a 1.5 × 1.5 × 1.0 m cuboid adiabatic sandbox with horizontal seepage, with the schematic diagram shown in Figure 15. To facilitate water seepage, two water chambers with a width of 0.15 m were constructed on opposite sides of the sandbox.…”
Section: Sandbox Experiments With Horizontal Seepagementioning
confidence: 99%
“…Duicu's study [4] reported the advantages of using heat pumps as a renewable source of energy. Different studies are also related to the employment of ground sources heat pumps [5]; in those applications, the performance of the entire heating and cooling system is significantly affected by soil thermal properties [6] and the circuit arrangement of the ground heat exchanger [7]. Regarding ASHP, in the recent literature, the effects of climate conditions are investigated by Mouzeviris and Papakostas [8] with reference to Greece.…”
Section: Introductionmentioning
confidence: 99%